Introduction to Self-optimization and Dependability - Trächtler, Ansgar; Hölscher, Christian; Rasche, Christoph; Priesterjahn, Claudia; Zimmer, Detmar; Henning Keßler, Jan; Stahl, Katharina; Flaßkamp, Kathrin; Vaßholz, Mareen; Krüger, Martin; Dellnitz, Michael; Iwanek, Peter; et al. (Dependability of Self-Optimizing Mechatronic Systems)

Methods of Improving the Dependability of Self-optimizing Systems - Seifried, Albert; Trächtler, Ansgar; Kleinjohann, Bernd; Heinzemann, Christian; Rasche, Christoph; Priesterjahn, Claudia; Steenken, Dominik; Ramming, Franz-Josef}; Wehrheim, Heike; Henning Keßler, Jan; Gausemeier, Jürgen; Stahl, Katharin; et al. (Dependability of Self-Optimizing Mechatronic Systems)

Analysis of Swarm Behaviors Based on an Inversion of the Fluctuation Theorem - Hamann, Heiko; Schmickl, Thomas; Crailsheim, Karl (Artificial Life)
A grand challenge in the field of artificial life is to find a general theory of emergent self-organizing systems. In swarm systems most of the observed complexity is based on motion of simple entities. Similarly, statistical mechanics focuses on collective properties induced by the motion of many interacting particles. In this article we apply methods from statistical mechanics to swarm systems. We try to explain the emergent behavior of a simulated swarm by applying methods based on the fluctuation theorem. Empirical results indicate that swarms are able to produce negative entropy within an isolated subsystem due to frozen accidents. Individuals of a swarm are able to locally detect fluctuations of the global entropy measure and store them, if they are negative entropy productions. By accumulating these stored fluctuations over time the swarm as a whole is producing negative entropy and the system ends up in an ordered state. We claim that this indicates the existence of an inverted fluctuation theorem for emergent self-organizing dissipative systems. This approach bears the potential of general applicability.

Self-Organized Collective Decision Making: The Weighted Voter Model - Dorigo, Marco; Hamann, Heiko; Valentini, Gabriele; Lomuscio, Alessio; Scerri, Paul; Bazzan, Ana; Huhns, Michael (Proceedings of the 13th Int. Conf. on Autonomous Agents and Multiagent Systems (AAMAS 2014))
Collective decision making in self-organized systems is challenging because it relies on local perception and local communication. Globally defined qualities such as consensus time and decision accuracy are both difficult to predict and difficult to guarantee. We present the weighted voter model which implements a self-organized collective decision making process. We provide an ODE model, a master equation model (numerically solved by the Gillespie algorithm), and agent-based simulations of the proposed decision-making strategy. This set of models enables us to investigate the system behavior in the thermodynamic limit and to investigate finite-size effects due to random fluctuations. Based on our results, we give minimum requirements to guarantee consensus on the optimal decision, a minimum swarm size to guarantee a certain accuracy, and we show that the proposed approach scales with system size and is robust to noise.

Evolving Prediction Machines: Collective Behaviors Based on Minimal Surprisal - Hamann, Heiko (Int. Conf. on Genetic and Evolutionary Computation (GECCO 2014))

Sorting in Swarm Robots Using Communication-Based Cluster Size Estimation - Birattari, Mauro; Dorigo, Marco; Hamann, Heiko; Garnier, Simon; Montes de Oca, Marco; Solnon, Christine; Stuetzle, Thomas; Ding, Hongli (Ninth Int. Conf. on Swarm Intelligence (ANTS 2014))

Derivation of a Micro-Macro Link for Collective Decision-Making Systems: Uncover Network Features Based on Drift Measurements - Khaluf, Yara; Dorigo, Marco; Hamann, Heiko; Valentini, Gabriele; Bartz-Beielstein, T. (13th International Conference on Parallel Problem Solving from Nature (PPSN 2014))

Evolution of Collective Behaviors by Minimizing Surprise - Hamann, Heiko; Sayama, Hiroki; Rieffel, John; Risi, Sebastian; Doursat, Rene; Lipson, Hod (14th Int. Conf. on the Synthesis and Simulation of Living Systems (ALIFE 2014))

A Swarm Robotics Approach to Task Allocation Under Soft Deadlines and Negligible Switching Costs - Cervera, Enric; Khaluf, Yara; Birattari, Mauro; Hamann, Heiko; Pobil, Angel P. del; Chinellato, Eris; Martinez-Martin, Ester; Hallam, John; Morales, Antonio (Simulation of Adaptive Behavior (SAB 2014))

A Review Corpus for Argumentation Analysis - Wachsmuth, Henning; Trenkmann, Martin; Stein, Benno; Engels, Gregor; Palakarska, Tsvetomira (Proceedings of the 15th International Conference on Intelligent Text Processing and Computational Linguistics)

Glycaemic index: did Health Canada get it wrong? Position from the International Carbohydrate Quality Consortium (ICQC). - Carbohydrate Quality Consortium, International; Jenkins, DJ; Willett, WC; Astrup, A; Augustin, LS; Baer-Sinnott, S; Barclay, AW; Björck, I; Brand-Miller, JC; Brighenti, F; Buyken, Anette; Ceriello, A; et al. (Br J Nutr)

Food intake and overweight in school-aged children in Germany: Results of the GINIplus and LISAplus studies. - Pei, Z; Flexeder, C; Fuertes, E; Standl, M; Buyken, Anette; Berdel, D; von Berg, A; Lehmann, I; Schaaf, B; Heinrich, J; and LISAplus Study Group, GINIplus (Ann Nutr Metab)

Are Requirements for Graduates of Master and PhD Programs in Business and Information Systems Engineering Changing? - Eymann, T.; Kundisch, Dennis

Should I Stay or Should I Go - Eymann, T.; Kundisch, Dennis; Recker, J.

Systematics of the virtual commissioning of automated production systems - Br {\ "o} kelmann, Jan

Holistic product protection management - approach to developing future- robust protection concepts - Eckelt, Daniel; Gausemeier, J {\ "u} rgen; Peter, Stefan (10th symposium f { \ "u} r Foresight and Technology Planning)

Business Model Patterns for Disruptive Technologies - Amshoff, Benjamin; Dülme, Christian; Echterfeld, Julian; Gausemeier, Jürgen

A Scalable Framework for Advanced Driver Assistance Systems Simulation - Abdelgawad, Kareem; Hassan, Bassem; Grafe, Michael; Gräßler, Iris

Telemedizinische Assistenzsysteme - Technik, Markt, Geschäftsmodelle - Gausemeier, Jürgen; Wolf, Bernhard; Clauss, Johannes; Friedrich, Petra; Herzog, Karolin; Lehner, Anne-Christin; Lehner, Markus; Placzek, Markus; Schierbaum, Thomas; Spittler, Thomas; Westermann, Thorsten

Method for the Identification and Comparison of Alternative Process Chains Focusing in Economics Effieciency Analysis During the Conceptual Design of Mechatronic Integrated Devices